Dysmenorrhea Exercise Affected The Level of Primary Menstrual Pain of Adolescents - Sirli Mardianna Trishinta; Pertiwi Perwiraningtyas; Susmini; Arnelia Pige (STIKes Patria Husada Blitar, 2023)
Primary menstrual pain can affect productivity and so it needs to reduce the pain. The purpose of this study was to determine the effect of dysmenorrhea exercise on the level of primary menstrual pain of teenager at the Akhlaqul Karimah Orphanage, Malang City. The design of this study used One-Group Pre-Post Test Design. The population of this study was all teenager at the Akhlaqul Karimah Orphanage, Malang City amounted to 17 people. The sample was all teenager at the Akhlaqul Karimah Orphanage Malang City experienced primary menstrual pain and adjusted to the inclusion criteria with a total of 14 people with purposive sampling technique. The data collection technique used an instrument in the form of a menstrual pain level questionnaire using a numeric rating scale (NRS) (pretest and post-test). Analysis of the data used Marginal Homogeneity. The results showed that the average level of dysmenorrhea pain before the implementation of dysmenorrhea exercise showed that almost half 7 respondents (37.5%) had moderate pain levels, 12 respondents (75.0%) had mild pain level. The results of the analysis of the Marginal Homogeneity test showed that p value = (0.000) < (0.05) so that H1 was accepted, meaning that there was an effect of dysmenorrhea exercise and drinking water on the level of primary menstrual pain of teenager at the Akhlaqul Karimah Orphanage City. Health workers are expected to be able to provide health information about prevention and management of dysmenorrheal pain with dysmenorrhea exercise as a non-pharmacological method.